PENINGKATAN HASIL BELAJAR SISWA MELALUI PENGGUNAAN METODE DEMONTRASI PADA MATA PELAJARAN PKN DI KELAS IV SD NEGERI 101770 TEMBUNG - Parida Hanom (Universitas Negeri Medan, 2022)
This study aims to use a demonstration approach in improving student learning outcomes in PKN subjects in grade IV SD Negeri 101770 Tembung, with the aim of improving student learning outcomes in PKN lessons. The subjects in this study were grade IV SD Negeri 101770 Tembung. In the even semester of the 2019/2020 school year (February to April 2020). The subjects in this classroom action research were all fourth grade students of SD Negeri 101770 Tembung, Percut Sei Tuan district, Deli Serdang Regency. For the 2019/2020 academic year, Medan has 28 students in cycle I, with details of 15 students (53.6 percent) getting a complete score and 13 students (46.4 percent) getting an incomplete score with an average score. 64.3. In this case the research was carried out in 2 (two) cycles, with research procedures including: conducting learning improvements, holding pretests (initial tests), providing motivation to students so that their scores meet completeness. The results showed that there was an increase in PKN learning outcomes through the use of the demonstration method.